Doing research with children a practical guide - Greig, Anne; Taylor, Jayne 1957-; MacKay, Tommy (SAGE, 2013)
"The Third Edition of Doing Research with Children is practical introduction to the process of designing, doing and writing up research with children and young people. At the center is a commitment to engaging with children and young people as active research participants rather than as passive subjects. In this new edition, you'll find up to date information on the fast-changing political and ethical debates around research with children and young people as well as guidance on how to carry out research yourself. Divided into three sections, the new edition covers: The main theories and approaches of research with children and young people ; Expanded guidance on research ethics ; Techniques for conduction both qualitative and quantitative research ; More on analyzing your research ; A brand new chapter on communicating your research findings. This is a must-have guide for students and practitioners who are engaging in research with children and young people."--Publisher's website.